Metagenomic analysis of orange colored protrusions from the muscle of Queen Conch Lobatus gigas (Linnaeus, 1758) (2018)
ABSTRACT: The endangered marine gastropod, Lobatus gigas, is an important fishery resource in the Caribbean region. Microbiological and parasitological research of this species have been poorly addressed despite its role in ecological fitness, conservation status and prevention of potential pathogenic infections. This study identified taxonomic groups associated with orange colored protrusions in the muscle of queen conchs using histological analysis, 454 pyrosequencing, and a combination of PCR amplification and automated Sanger sequencing. The molecular approaches indicate that the etiological agent of the muscle protrusions is a parasite belonging to the subclass Digenea. Additionally, the scope of the molecular technique allowed the detection of bacterial and fungi clades in the assignment analysis. This is the first evidence of a digenean infection in the muscle of this valuable Caribbean resource.